Assessment of clinician well-being and the factors that influence it using validated questionnaires: a systematic review - Claudie Audet; Andréanne Bernier; Marimée Godbout-Parent; Hermine Lore Nguena Nguefack; Liz Ferland; Paula L. Bush; Marie-Dominique Poirier; Sonia Lussier; Tracie A. Barnett; Sylvie D. Lambert; Anaïs Lacasse (Communications Medicine)
Abstract Background Measuring clinician experiences of care and well-being (e.g. job satisfaction, fulfillment) offers insights into the practice environment’s impact, aiding workforce retention, patient safety, and care quality. However, valid measurement instruments are essential. This systematic review identified validated self-reported questionnaires designed to assess clinician well-being and its influencing factors. Methods Psychometric studies in English or French on measurement instruments addressing factors that influence clinician well-being, as proposed by the National Academy of Medicine, were included. Studies published between 2013 and 2023 were retrieved in December 2023 by searching these databases: CINAHL, Embase, HaPI, MEDLINE, PsycINFO, Mental Measurements Yearbook, and APA PsycTests. Study selection was completed by two independent reviewers. Results were summarized narratively, in tables, and figures. Quality of psychometric studies was assessed by the number of measurement properties addressed. The review protocol was registered with INPLASY® (202410047). Results Out of 10,441 records identified, 136 studies are included. The majority come from the USA (27.2%), Spain (11.0%), Canada (5.9%), or Australia (5.9%). Most focus on instruments for clinicians, regardless of their specialty (55.9%). Among profession-specific instruments (44.1%), nurses and physicians are mainly targeted. The most common domains are: (1) ‘Learning/practice environment’ (38.2%), (2) ‘Healthcare responsibilities’ (21.3%), and (3) ‘Organizational factors’ (19.1%). The most frequently addressed measurement properties are: (1) Internal consistency (88.2%), (2) Structural validity (75.7%), and (3) Content validity (68.4%). Conclusions Many tools for measuring clinician well-being exist, but few are fully validated. The results of this review provide a foundation to support ongoing psychometric evaluation and cross-cultural adaptation.